EVALUASI KUALITAS FITUR LAYANAN APLIKASI CUSTOMER INFORMATION SYSTEM (CIS) PDAM SURYA SEMBADA KOTA SURABAYA MENGGUNAKAN METODE E-SERVQUAL - Adelia Desi Agnesita; Hawwin Mardhiana; Aris Kusumawati (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
PDAM Surya Sembada Surabaya has developed the Customer Information System (CIS) application since 2013 to facilitate bill payment transactions and complaints about water problems and so on. Despite more than 100,000 downloads, some users complained about the service, including problems recording water meters and failures when registering. Therefore, it is necessary to evaluate the quality of service on the CIS PDAM Surya Sembada Kota Surabaya application using E-Service Quality (E-Servqual) to measure the level of user satisfaction. This method is a measurement dimension to determine service quality which focuses more on electronic services. E-Servqual generally provides how well a company is able to meet customer needs through the use of electronic facilities. This evaluation is needed to find areas of improvement to increase user satisfaction. The aim of this research is to identify factors that influence user satisfaction of CIS PDAM Surya Sembada Surabaya City and provide recommendations for service improvements. This research uses quantitative methods by collecting data through surveys and applying purposive sampling techniques based on primary data obtained through questionnaires given to respondents. -From the analysis it was found that the dimensions of efficiency, system availability, compliance, privacy, responsiveness and compensation did not have a positive and significant impact on user satisfaction. However, the contact dimension has a patch coefficient value of 0.764, a t-statistic value of 9.714 (>1.98) and a p-value of 0.000 (<0.05) indicating that the contact variable has a positive and significant effect on user satisfaction. The ability to contact PDAM service centers via the CIS application has a positive and significant impact, demonstrating the importance of easy and effective access to customer service to increase user satisfaction.